Knowledge Hiding Trends: Systematic Literature Review (SLR) - Annisa Sari; Joko Suyono (Jurnal Syntax Transformation, 2024)
This research was conducted by systematic literature review (SLR) analysis using PRISMA assistance in Watase. The purpose of this study is to answer questions related to the trend of knowledge hiding in the last five years. To find out this, this study uses grounded theory which helps in the development of SLR content analysis. The results obtained are that it can be seen that the knowledge hiding is a topic that is of great interest to researchers for further research. This can also be seen from the increase in knowledge hiding articles every year. This study also shows some recommendations obtained from the limitations of previous studies that can help future researchers in exploring and developing research related to knowledge hiding.